Attachment Security and the Social World - Sochos, A. author. aut Link
VI, 189 p.
Keywords: With an overview of the existing attachment theory literature and new contributions to the field, this book proposes that social groups seek protection and security as they collectively construct their ideologies and social institutions. In doing so, the book extends attachment theory to show how it can inform wider socio-cultural phenomena.